UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI PENDEKATAN PAKEM DENGAN MEDIA INTERAKTIF - Hartati, Risma (Unversitas Katolik Santo Thomas, 2022)
ABSTRACT The purpose of this research is to improve social studies learning outcomes through a standard approach with interactive media with the sub-theme of work around me. The low social studies learning outcomes with the sub-theme of work around me became one of the things found. The subjects in this study were fourth grade students of SD Private Bersinar with a total of 21 students using Classroom Action Research. The results obtained in the first cycle. The learning outcomes in the first cycle were 11 students or 52.38% of students who had not reached the KKM and 10 students or 47.62% of students who had reached the KKM. The average student learning outcomes are 67. However, in the improvement of teaching and learning in the second cycle, 19 students or 90.47% of students have reached the KKM and 2 students or 9.53% of students have not reached the KKM. The average student learning outcomes are 78. The implementation of learning has increased from 59.8% (enough category) to 79.5% (good category).